The moderating role of trait online disinhibition in exacerbating the online victim-bully cycle - K TENNAKOON APPUHAMILLAGE KASTURIRATNA, Sandeeshwara (Institutional Knowledge at Singapore Management University, 2024)
The growth of the internet and social media as a communication platform has increased the incidence of cyberbullying victimisation. While there has been increasing research interest on the antecedents of cyberbullying perpetration, little is known on why some individuals who themself experience cyber victimisation are more likely to become cyberbullying perpetrators. Considering the large number of individuals who experience cyberbullying victimisation in the current, highly digitalised world, this trend of victims turning into bullies poses a worrisome possibility and deserves research attention. One promising individual difference that could potentially moderate the relationship between cyberbullying victimisation can lead to cyberbullying perpetration is trait online disinhibition, the idea that people separate their online and offline lives, and experience a reduced sense of responsibility for their online actions. As such, the current study utilised data from a large sample of young adults (N = 259) in order to examine the exacerbating role of trait online disinhibition on the relationship between cyberbullying victimisation and cyberbullying perpetration. Regression analysis indicated that individuals with high trait online disinhibition were significantly more likely to become cyberbullying perpetrators after being victimised. These findings underscore the importance of addressing online disinhibition tendencies in order to break the victim-bully cycle and emphasise the need for developing features and guidelines aimed at reducing features such as perceptions of anonymity that contribute to disinhibition on online platforms.